Creating a Golden Generation through Classroom Management and Positive Discipline Workshop at SIT Nurul Fikri Makassar - Hastina; Muali, Nurfatihah Fauziah; Nawir, Muhammad Syahruddin (IJOCSE: Indonesian Journal of Community Services, 2024)
Education is the main key to building a golden generation for the nation. Sekolah Islam Terpadu (SIT) Nurul Fikri Makassar is committed to creating a golden generation through student development programs, including the Classroom Management and Positive Discipline Workshop. This workshop aims to improve teachers’ knowledge and skills in managing classes and implementing positive discipline. The workshop was attended by several SIT Nurul Fikri Makassar teachers, with material covering the concepts of effective classroom management, positive discipline strategies, and their implementation practices. The results of the workshop showed an increase in teacher understanding of classroom management and positive discipline, as well as motivation to implement the strategies learned. In addition, the workshop at SIT Nurul Fikri Makassar was effective in improving teachers’ knowledge and skills, and teachers were more motivated to manage classes effectively and implement positive discipline, with the hope of creating a golden generation that is intelligent, creative, and has character.